![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
1.
b) \(B=\left|x+8\right|+\left|x+18\right|+\left|x+50\right|\)
Ta có:
\(B=\left|x+8\right|+\left|x+18\right|+\left|x+50\right|\ge\left(\left|x+8\right|+\left|-50-x\right|\right)+\left|x+18\right|\)
\(\Rightarrow B=\left(\left|x+8-50-x\right|\right)+\left|x+18\right|\)
\(\Rightarrow B=\left|-42\right|+\left|x+18\right|\)
\(\Rightarrow B=42+\left|x+18\right|\ge42\)
\(\Rightarrow MIN_B=42\) khi và chỉ khi:
\(\left\{{}\begin{matrix}x+8\ge0\\x+18=0\\x+50\ge0\end{matrix}\right.\Rightarrow\left\{{}\begin{matrix}x\ge-8\\x=-18\\x\ge-50\end{matrix}\right.\Rightarrow x=-18.\)
Vậy \(MIN_B=42\) khi \(x=-18.\)
3.
b) \(\left|x-3\right|-\left|2x+1\right|=0\)
\(\Rightarrow\left|x-3\right|=\left|2x+1\right|\)
\(\Rightarrow\left[{}\begin{matrix}x-3=2x+1\\x-3=-2x-1\end{matrix}\right.\Rightarrow\left[{}\begin{matrix}x-2x=1+3\\x+2x=\left(-1\right)+3\end{matrix}\right.\Rightarrow\left[{}\begin{matrix}-1x=4\\3x=2\end{matrix}\right.\)
\(\Rightarrow\left[{}\begin{matrix}x=4:\left(-1\right)\\x=2:3\end{matrix}\right.\Rightarrow\left[{}\begin{matrix}x=-4\\x=\frac{2}{3}\end{matrix}\right.\)
Vậy \(x\in\left\{-4;\frac{2}{3}\right\}.\)
Chúc bạn học tốt!
![](https://rs.olm.vn/images/avt/0.png?1311)
c) l x - 5 l = 2x
\(\Leftrightarrow\orbr{\begin{cases}x-5=2x\\x-5=-2x\end{cases}}\)
\(\Leftrightarrow\orbr{\begin{cases}x-2x=5\\x+2x=5\end{cases}}\)
\(\Leftrightarrow\orbr{\begin{cases}-x=5\\3x=5\end{cases}}\)
\(\Leftrightarrow\orbr{\begin{cases}x=-5\\x=\frac{5}{3}\end{cases}}\)
Hok tốt!!!!!!!
Tìm x, biết:
a) |2x + 1| = 17
<=>\(\orbr{\begin{cases}2x+1=17\\2x+1=-17\end{cases}}\)
<=>\(\orbr{\begin{cases}2x=16\\2x=-18\end{cases}}\)
<=> \(\hept{\begin{cases}x=8\\x=-9\end{cases}}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\left|x\right|=7\)
\(\Rightarrow\orbr{\begin{cases}x=7\\x=-7\end{cases}}\)
Vậy \(x\in\left\{\pm7\right\}\)
\(\left(\frac{1}{2}\right)^x\)+ \(\left(\frac{1}{2}\right)^{x+4}\)= 17
\(\Rightarrow\)\(\left(\frac{1}{2}\right)^x\)+ \(\left(1+\left(\frac{1^4}{2}\right)\right)\)= 17
\(\Rightarrow\)\(\left(\frac{1}{2}\right)^x\)\(.\frac{17}{16}\)= 17
\(\Rightarrow\)\(\left(\frac{1}{2}\right)^x\)= 16
\(\Rightarrow\)\(\left(\frac{1}{2}\right)^x\)= \(\left(\frac{1}{2}\right)^{-4}\)
\(\Rightarrow\)\(x=-4\)
Vậy \(x=-4\)